2014
DOI: 10.1007/s00125-014-3457-8
|View full text |Cite|
|
Sign up to set email alerts
|

Low-energy diets differing in fibre, red meat and coffee intake equally improve insulin sensitivity in type 2 diabetes: a randomised feasibility trial

Abstract: Aims/hypothesis Epidemiological studies have found that a diet high in fibre and coffee, but low in red meat, reduces the risk for type 2 diabetes. We tested the hypothesis that these nutritional modifications differentially improve whole-body insulin sensitivity (primary outcome) and secretion. acarbose and known disease duration of ≤5 years. Exclusion criteria were: HbA 1c >75 mmol/mol (9.0%), type 1 or secondary diabetes types and acute or chronic diseases including cancer. Patients taking any medication af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 37 publications
2
45
0
1
Order By: Relevance
“…Multiple linear regression analyses with adjustments for sex, age, and BMI were performed to determine associations between two variables. The primary outcome for this pilot study was the change in whole-body insulin sensitivity to obtain effect size and variance estimates for both diets (20). The primary outcome measures were pNN50 (representing the time-domain HRV measures) and low-frequency/high-frequency ratio (representing the frequency-domain HRV measures).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Multiple linear regression analyses with adjustments for sex, age, and BMI were performed to determine associations between two variables. The primary outcome for this pilot study was the change in whole-body insulin sensitivity to obtain effect size and variance estimates for both diets (20). The primary outcome measures were pNN50 (representing the time-domain HRV measures) and low-frequency/high-frequency ratio (representing the frequency-domain HRV measures).…”
Section: Discussionmentioning
confidence: 99%
“…The details of the study protocol have been reported elsewhere (20). In brief, volunteers invited to the German Diabetes Center were 1:1 randomly allocated to one of two dietary interventions using randomization blocks (four or six patients) with consecutive numbers.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations